Analysis of the differences between the Educational Technology Area (AECT) and the Concept of Learning Media (Elkom: Jurnal Elektronika dan Komputer, 2026)
The rapid advancement of technology in the modern era has significantly transformed the educational landscape, yet conceptual ambiguity remains regarding the relationship between Educational Technology and Learning Media. Many educators mistakenly perceived Educational Technology as merely the use of instructional tools or aids. This study aimed to analyze the fundamental differences between the domains of Educational Technology according to AECT (Association for Educational Communications and Technology) standards and the concept of Learning Media, specifically focusing on their scope, functions, and systemic approaches. The research employed a descriptive analysis of core theories and the evolution of AECT definitions. The results indicated that Educational Technology is a comprehensive and systematic system encompassing five major domains: design, development, utilization, management, and evaluation. Conversely, Learning Media serves as a specific component within the utilization domain, acting as a vehicle for message delivery. This study concluded that Educational Technology is a holistic systematic approach to solving learning problems, whereas media is a supporting tool within that system. A precise understanding of these differences is essential for educators to design more effective, efficient, and relevant instructional strategies in facing the challenges of the digital era.